2017
DOI: 10.7717/peerj.3260
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and evaluation of reference genes for quantitative real-time PCR analysis inAmorphophallus

Abstract: Quantitative real-time reverse transcription PCR (RT-qPCR) has been widely used in the detection and quantification of gene expression levels because of its high accuracy, sensitivity, and reproducibility as well as its large dynamic range. However, the reliability and accuracy of RT-qPCR depends on accurate transcript normalization using stably expressed reference genes. Amorphophallus is a perennial plant with a high content of konjac glucomannan (KGM) in its corm. This crop has been used as a food source an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 65 publications
0
15
1
Order By: Relevance
“…We found that the two algorithms produced the same ranking of the reference genes according to the differences in the stability (Table 2 and Fig. Many studies revealed that using a combination of multiple top stable reference genes might improve the reliability of gene expression by RT-qPCR [20,41]. The NormFinder analysis showed that HuUBQ and HuUQT were the two top stable reference genes in all of the experimental samples, while HuACT (under salt stress, drought stress, and different cultivars) and Hu18S rRNA (under heat stress and different tissues) were the most unstable reference genes.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…We found that the two algorithms produced the same ranking of the reference genes according to the differences in the stability (Table 2 and Fig. Many studies revealed that using a combination of multiple top stable reference genes might improve the reliability of gene expression by RT-qPCR [20,41]. The NormFinder analysis showed that HuUBQ and HuUQT were the two top stable reference genes in all of the experimental samples, while HuACT (under salt stress, drought stress, and different cultivars) and Hu18S rRNA (under heat stress and different tissues) were the most unstable reference genes.…”
Section: Discussionmentioning
confidence: 86%
“…The expression stabilities of these genes were found to be different in different species as well as different experimental conditions in the same species [5,9,20,22]. The expression stabilities of these genes were found to be different in different species as well as different experimental conditions in the same species [5,9,20,22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Elongation factor EF1 has been reported to be the most stable gene in terms of expression in peanut under cold treatment (Chen et al 2011, Chi et al 2012, and in switch grass (Huang et al 2014a) and African oil palm (Xia et al 2014) under abiotic stresses. The expression stability of genes is related to the function they play in biological metabolic pathways (Wang et al 2017). Ubiquitin is a small protein existing in all eukaryotes with a conserved sequence and structure, which plays important roles in controlling cellular signal transduction (Zhang 2011).…”
Section: Discussionmentioning
confidence: 99%